Bibliometric analysis of the progress and thematic patterns of stem cell research applied to plastic surgery - Jiménez-Hilarion, Laura M. (2025)
Objective: To determine the progress and research patterns on stem cells applied to plastic surgery. Methods: Cross-sectional bibliometric study. A semi-structured search was conducted in the Scopus database. Results: A total of 1,735 articles were included, with the first publication appearing in 1986. Notable growth in publication frequency was observed only after 2005. The scientific output predominantly consisted of original articles (66.5%; n=1,146), followed by reviews (27.9%; n=484). International collaboration was at 22.7%. The University of Michigan and the United States are the most prolific institution and country with the highest impact to date, respectively. The United States, the United Kingdom, China, and Japan are the countries with the most international collaboration. Regarding research patterns, tissue engineering, guided tissue regeneration, cell differentiation, stem cell transplantation, and adipose tissue have been the most studied topics. Visually, it was revealed that research on stem cell transplantation and deep learning applied to adipose cells are novel research niches. Conclusion: Research on stem cells applied to plastic surgery has experienced gradual growth, with a noticeable increase in recent years. The integration of artificial intelligence, tissue engineering, and stem cell transplantation are the emerging research niches to date. Mainly, this field has focused on guided tissue regeneration and cell differentiation.